"Benches become like porches": Built and social environment influences on older adults' experiences of mobility and well-being. (November 2016) - Ottoni, Callista A.; Sims-Gould, Joanie; Winters, Meghan; Heijnen, Myrthe; McKay, Heather A.
Abstract: Neighbourhood environments significantly influence health and well-being, especially as people age. Our study uniquely highlights how one microscale feature (benches) influence older adults experiences of mobility and well-being, from their perspective. We also explore how these experiences affect and are affected by the social environment of the neighbourhoods where older adults live. We conducted one-on-one seated and walk-along interviews with individuals aged 60+ that live in three adjacent neighbourhoods in Vancouver, Canada. We collected data at two time points (n = 28, 2012; n = 22, 2014). We found that benches positively contributed to older adults' mobility experiences by: (i) enhancing their use and enjoyment of green and blue spaces, (ii) serving as a mobility aid, and (iii) contributing to social cohesion and social capital. To address the increased needs of an aging demographic, urban planners might consider the quality and presence of microfeatures as part of an immediate and inexpensive strategy to create supportive neighbourhoods for people of all ages and abilities. Highlights: Neighbourhood environments influence health and well-being as people age. There are strong interconnections between built and social environments. Microscale features can enable older adults' to accommodate to their abilities. Benches can promote mobility and social connectedness for older adults. Microscale features, like benches, are a prudent investment for communities.